2022
DOI: 10.3390/plants11050580
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Anatomical Characteristics and Transcriptomic Differences between Heterografts and Homografts in Pyrus L.

Abstract: Pear (Pyrus L.) is an important temperate fruit worldwide, and grafting is widely used in pear vegetative propagation. However, the mechanisms of graft healing or incompatibility remain poorly understood in Pyrus. To study the differences in graft healing in Pyrus, the homograft “Qingzhen D1/Qingzhen D1” and the heterograft “QAUP-1/Qingzhen D1” as compatibility and incompatibility combinations were compared. Anatomical differences indicated the healing process was faster in homografts than in heterografts. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These are key points to improve the survival rate of grafting [50] . The high survival rate of reciprocal grafted plants is also related to the positive expression of cell wall related genes [51,52] . Our results found that the expression levels of PtrXTH22 and PtrXTH17 in the low survival rate grafted combination S/P were higher than those in the high survival rate grafted combination, which may play an important regulatory role in the healing process of S/P grafting.…”
Section: Discussionmentioning
confidence: 99%
“…These are key points to improve the survival rate of grafting [50] . The high survival rate of reciprocal grafted plants is also related to the positive expression of cell wall related genes [51,52] . Our results found that the expression levels of PtrXTH22 and PtrXTH17 in the low survival rate grafted combination S/P were higher than those in the high survival rate grafted combination, which may play an important regulatory role in the healing process of S/P grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Grafting is an ancient horticultural technology widely used to improve yield, quality, and stress tolerance. [ 3 ] It has been widely used in the cultivation and variety improvement of horticultural crops and has created substantial economic value. [ 4 ] Graft union healing is the key to the survival of grafted seedlings, and it is a critical problem to realize the improved properties of grafts.…”
Section: Introductionmentioning
confidence: 99%